ANALISIS RISIKO STUNTING TERHADAP POLA ASUH PADA BALITA DI WILAYAH KERJA PUSKESMAS SIAK KABUPATEN SIAK - Masyitha Ramadhani; Riski Novera Yenita (STIKes Al-Insyirah Pekanbaru, 2022)
The prevalence of stunting in Siak Regency reached 21.0%. Prevalence of stunting becomes a public health problem if it reaches 20% and needs to be handled before it increases. The general understanding in alleviating stunting is to focus on health efforts which are risk factors. Whereas risk factors are strongly influenced by protective factors including parenting / family. Stunting will have an impact not only physically, but also on cognitive function. This study aims to determine whether there is a relationship between feeding parenting and the incidence of stunting. The research design used is quantitative with a cross sectional analytic survey. The research subjects were mothers who had stunted toddlers aged 24-59 months, namely 49 respondents who were the case group, and 49 non-stunted toddlers who were the control group using total sampling. Data analysis used was Chi-square statistical test with a significance level of 0.05. The results of the relationship test showed that p-value = 0.000 (p <0.05), then there was a relationship between feeding parenting (democratic, authoritarian, permissive, and neglectful) with the incidence of stunting.It is recommended for puskesmas officers that the results of this study can be used as guidelines for providing counseling on good maternal behavior in preparing food and collaborating with relevant agencies that can help improve nutrition for children under five.